Short communicationTwo-vessel chronic total occlusion. Complete percutaneous revascularisation - Dębski, Artur; Tyczyński, Paweł; Opolski, Maksymilian P.; Kłopotowski, Mariusz; Karcz, Maciej A.; Witkowski, Adam (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Little is known about the success rate of second attempts to open chronic total occlusions. Two-vessel occlusion makes the procedure is even more challenging. Thus, embarking on complete percutaneous revascularization of such lesions requires adequate experience, especially after first unsuccessful attempt. We present a case of a 52-year-old male patient in whom successful percutaneous opening of two chronic coronary at staged procedure was performed.